2022
DOI: 10.1080/19490976.2022.2110639
|View full text |Cite
|
Sign up to set email alerts
|

Akkermansia muciniphila upregulates genes involved in maintaining the intestinal barrier function via ADP-heptose-dependent activation of the ALPK1/TIFA pathway

Abstract: The commensal bacteria that make up the gut microbiota impact the health of their host on multiple levels. In particular, the interactions taking place between the microbe-associated molecule patterns (MAMPs) and pattern recognition receptors (PRRs), expressed by intestinal epithelial cells (IECs), are crucial for maintaining intestinal homeostasis. While numerous studies showed that TLRs and NLRs are involved in the control of gut homeostasis by commensal bacteria, the role of additional innate immune recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 50 publications
2
18
0
Order By: Relevance
“… 17 37 The mechanism by which A. muciniphila protects the intestine from emulsifiers remains to be defined but might involve membrane-associated Amuc_100, 17 38 secreted P9, 19 membrane-associated phospholipid diacyl phosphatidylethanolamine, 39 and/or the ADP-heptose-like molecule, recently identified as being released by A. muciniphila with the ability to modulate the NF-kB signalling pathway. 40 Moreover, accumulating evidence suggest that A. muciniphila interaction with the host involves TLR2-signalling pathways 17 39 as well as modulation of IL10 and IL22 cytokines. 41 42 Thus, future studies to identify the mechanism at play during protection against emulsifier-induced metabolic deregulations are warranted.…”
Section: Discussionmentioning
confidence: 99%
“… 17 37 The mechanism by which A. muciniphila protects the intestine from emulsifiers remains to be defined but might involve membrane-associated Amuc_100, 17 38 secreted P9, 19 membrane-associated phospholipid diacyl phosphatidylethanolamine, 39 and/or the ADP-heptose-like molecule, recently identified as being released by A. muciniphila with the ability to modulate the NF-kB signalling pathway. 40 Moreover, accumulating evidence suggest that A. muciniphila interaction with the host involves TLR2-signalling pathways 17 39 as well as modulation of IL10 and IL22 cytokines. 41 42 Thus, future studies to identify the mechanism at play during protection against emulsifier-induced metabolic deregulations are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of tight junctions between intestinal epithelial cells is determined by the proliferation capacity of intestinal epithelial cells and the expression level of tight junction proteins. It has been reported that A. muciniphila upregulates MUC2, BIRC3 and TNFAIP3 (BIRC3 and TNFAIP3 are anti-apoptotic genes of intestinal epithelial cells involved in their proliferation process) via ADP-heptose-dependent activation of the ALPK1/TIFA pathway, which maintains intestinal barrier function and reduce its permeability ( 93 ). This subsequently inhibits chronic low-grade inflammation induced by LPS and insulin resistance.…”
Section: The Utility Of a Muciniphila In Metabolic...mentioning
confidence: 99%
“…For example, Akk colonization alleviates high-fructose- and restraint-stress-induced jejunal mucosal barrier disruption by enhancing the function of NLRP6, promoting autophagy, maintaining the normal secretion of antimicrobial peptides in Paneth cells, promoting the expression of tight junction proteins, negatively regulating the NF-kB signaling pathway, and inhibiting the expression of inflammatory cytokines [ 166 ]. A recent report suggests that Akk upregulates genes involved in maintaining the intestinal barrier function via ADP-heptose-dependent activation of the ALPK1/TIFA pathway, which indicates that Akk promotes intestinal barrier homeostasis by activating an innate immune response [ 167 ]. Amuc-1100 promotes IL-10 production by activating TLR2 and TLR4 and eventually activates the NF-kB pathway to promote the production of cytokines [ 168 ].…”
Section: Akkermansia Muciniphila : Interaction With Intestin...mentioning
confidence: 99%